2020
DOI: 10.1108/bfj-03-2020-0261
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age differences in the relationship between calorie, macronutrients intake and growth status of school-aged Aboriginal children at Labu, Negeri Sembilan

Abstract: PurposeThis study aimed to determine the relationship between calorie and macronutrients intake and the growth status of Aboriginal children based on gender and age group.Design/methodology/approachThis was a cross-sectional study participated by 85 school-aged Aboriginal children at Labu, Negeri Sembilan. The dietary intake and socioeconomic status data were collected from the parents using an interviewer administrated structured-questionnaire and 24-hour dietary recall. WHO AnthroPlus software was used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
1
7
1
Order By: Relevance
“…Elder children in this study may have a lesser screen time and engage in physical activities such as cycling more often due to limited access to gadgets and other technological appliances. In addition, Kuralneethi et al ( 31 ) reported a similar finding which highlighted that there were no significant differences between BAZ with age and gender of aborigine children in that study. Moreover, the authors also stated that the insignificant differences between both genders were evident as the dietary intakes between both genders were similar.…”
Section: Discussionsupporting
confidence: 63%
“…Elder children in this study may have a lesser screen time and engage in physical activities such as cycling more often due to limited access to gadgets and other technological appliances. In addition, Kuralneethi et al ( 31 ) reported a similar finding which highlighted that there were no significant differences between BAZ with age and gender of aborigine children in that study. Moreover, the authors also stated that the insignificant differences between both genders were evident as the dietary intakes between both genders were similar.…”
Section: Discussionsupporting
confidence: 63%
“…The adequacy of macronutrients and micronutrients indicated an important key in dietary quality, especially among school-aged children who undergo rapid physical growth (Karim and Razak, 2019;Kuralneethi et al, 2020;Shan et al, 2018). The dietary energy and carbohydrates intake were low among the aboriginal than recommended intake, which could be due to poor cereals and grains food group intake by the aboriginal children (Cordelia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, no study been published on the diet quality of aboriginal school children in Malaysia. Moreover, to the best of our knowledge, most of the growth status and nutrient intake studies (Chua et al, 2012;Cordelia et al, 2019;Murtaza et al, 2018Murtaza et al, , 2019 in Malaysia were conducted only among preschool-age or younger aboriginal children than school-aged children (Kuralneethi et al, 2020). Thus, the present study was carried out to determine the dietary quality of aboriginal school children and its association with their growth status.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations